Promoting women in urology using the example of habilitation - Welte, Maria-Noemi; Knipper, Sophie; Siech, Carolin; Greiser, Eva Maria; Wiemer, Laura; Mueller, Karina; Bellut, Laura; Walach, Margarete Teresa; Herlemann, Annika; Weinberger, Sarah (Die Urologie, 2022)
Background The proportion of female urologists is steadily increasing, yet they continue to be underrepresented in academic leadership positions. A postdoctoral lecture qualification (habilitation), which is mandatory for a successful scientific career, is achieved significantly less often by female urologists in Germany than by their male colleagues. Objective To identify factors to effectively promote female urologists into academic leadership positions, the current situation, as well as factors influencing successful habilitation of women who are members of the German Society of Urology (Deutsche Gesellschaft fur Urologie [DGU]) were investigated. Methods An online questionnaire was distributed to 1343 female members of the DGU in Germany, Austria, and Switzerland. The responses of 521 women were statistically analyzed with respect to baseline characteristics and in relation to research funding. The primary endpoint of our study was the habilitation rate. Results The average age of the 521 participating female urologists who completed the questionnaire was 37 years (range 21-67 years). Of these, most female physicians were in postgraduate training (n = 168, 32%), worked full-time (n = 324, 62%), and had children (n = 277, 53%). Overall, 359 (69%) of the participants had a PhD and 63 (12%) were still working on their PhD. Thirty (5.8%) female urologists had a habilitation. In univariable logistic regression models, age (odds ratio [OR] 1.06), working time model (part-time OR 0.19), a research fellowship (OR 21.4), release from clinical work for research purposes (OR 13.7), and participation in a funding program (OR 6.9) or mentoring program (OR 7.0) were independent predictors of achieving habilitation. Whether a urologist had children was not an independent predictor of achieving habilitation. In multivariable logistic regression models, age (OR 1.08), and a research fellowship (OR 9.04) were independent predictors of achieving habilitation. Conclusions Promoting habilitation among female urologists is required in order to increase the proportion of women in leading academic positions. The results of the data analysis show that the promotion of research fellowships explicitly for women could be a promising approach.
CRIS-Team WoS Importer:2022-08-19